E-learning System Acceptance Factors for Training: A Study of Employees Perception in Tourism Industry - MORADI, Leila; YAHYA, Yazrina; MOHAMED, Ibrahim; RAISIAN, Komeil (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017DO - 10.14505//jemt.v8.6(22).12, 2018)
Training is critical in tourism industry to stay ahead of competitors. Having state of art technology and Internet set foundation for e-learning systems for training purposes. This paper focuses on the acceptance of e-learning systems for training in e-tourism companies. Building upon TAM, a framework is developed and survey helps to provide evidence for present research. Findings emphasize on the necessity of computing experience, attitude, and motivation among employees to accept e-learning systems as a tool of training. Finally, the success of e-training lies in the hand of every single individual within organization and the discussion is available.